The effect of social information on the collective choices of ant colonies. (8th February 2016) - Burns, Dominic D.R.; Sendova-Franks, Ana B.; Franks, Nigel R.
Lay Summary: Sharing social information through recruitment can alter the outcome of collective decisions. We show that when ants share social information through recruitment, colonies consistently choose a nest site that fluctuates between being good and bad over a constantly mediocre alternative, even when the latter is the better option for longer. This choice contrasts with previous results showing colonies can accurately assess nest sites that fluctuate in quality when recruitment is infrequent. Twitter: @Domburnsburns Abstract: In collective decision making, groups collate social information to inform their decisions. Indeed, societies can gather more information than individuals—so social information can be more reliable than private information. Colonies of Temnothorax albipennis can estimate the average quality of fluctuating nest sites when the sharing of social information through recruitment is rare. However, collective decisions in T. albipennis are often reached with the use of recruitment. We use a new experimental setup to test how colonies react to fluctuating nest sites when they use recruitment to reach a decision. When recruitment is used, colonies consistently choose nest sites that fluctuate between being "good" and "poor" over constantly "mediocre" alternatives. Moreover, they do so even if the fluctuating option is only "good" for 25% of the time. The ants' preference for fluctuating nest sites appears to be due to tandem running. Even if a nest site is only briefly "good, " scouts that experience it when it is "good" are likely to perform tandem runs to it. However, a constantly "mediocre" nest site is unlikely to ever provoke tandem runs. Consequently, the fluctuating nest sites attracted more tandem runs, even when they were only "good" for a short time. This led to quorum attainment in fluctuating nest sites rather than in constant "mediocre" nest sites. The results of this experiment demonstrate how sharing of social information through recruitment can change the outcome of collective decisions.